THE PREVENTION OF CORRUPTION RISK THROUGH THE IMPROVEMENT OF OPEN SELECTION SYSTEM FOR TOP LEADERSHIP POSITION IN LOCAL GOVERNMENT - Abdul Aziz (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
ABSTRACTThrough the Regulation of the Minister of State Apparatus Empowerment (Permenpan) no 13 of 2014, the government has changed and imposed a new system in the placement of the top leadership position by applying an open promotion system. However, this system is still considered providing space for the risk of corruption, especially in local governments. The main purpose of this study is to review the rules underlying the implementation of open promotion in local government and provide an idea for the improvement of this system. This study uses a qualitative approach in which the data collection is conducted through interviews, observations and documentation. The results of this study indicate that the procedures and mechanisms of the implementation of open promotion for the top leadership position in local governments still provide spaces for corruption, such as in the formation of selection committees, mechanisms in determining the selection results, and monitoring and evaluation mechanisms. In addition, it is necessary to integrate the implementation of promotion of the top leadership positions, both in central and in local governments. In conclusion, a number of inputs that can be put forward include the enhancement of the function of the State Civil Service Commission (better known in Indonesia as KASN) in monitoring the implementation of open promotion of top leadership position in local government. As a preventive measure, the implementation of open promotion can be developed through electronic systems.